Comparison of agricultural payments and income of the cereals sector - Lipcsei, József (Studia Mundi – Economica, 2020)
The diversity of agricultural subsidies gives farmers a choice to apply organic, economic or combined farming methods. The professional interpretation of area payments can be broad. It is also possible to claim priority titles for the purpose of maximizing aid, while avoiding intensive production. In my paper, I would like to point out the extremes between supplementary titles, production income and some elements of the wage table.